Respostas
respondido por:
2
x²-8x+12=0
(-8)²-4.1.12
64-48
16
-(-8)+-√16
--------------
2.1
8+-4
--------
2
8+4
------ = 6
2
8-4
----- = 2
2
(-8)²-4.1.12
64-48
16
-(-8)+-√16
--------------
2.1
8+-4
--------
2
8+4
------ = 6
2
8-4
----- = 2
2
respondido por:
2
X²-8x+12=0
Δ= 8²-4.1.12
Δ=64-48=16
x'= 8 -√16
2
x'=8-4= 2=1
2 2
x''=8+4= 12= 6
2 2
s{ 1,6 }
Δ= 8²-4.1.12
Δ=64-48=16
x'= 8 -√16
2
x'=8-4= 2=1
2 2
x''=8+4= 12= 6
2 2
s{ 1,6 }
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás